Theoretical and experimental studies on liquid refractive index sensor based on bundle fiber - Harun, Sulaiman Wadi; Yang, Hang Zhou; Ahmad, Harith (Emerald, 2011)
Purpose - The purpose of this paper is to investigate, theoretically and experimentally the performance of liquid refractive index sensor (LRIS). Design/methodology/approach - The proposed LRIS is based on the intensity modulation and a bundle fiber. The mathematical model is used to study the effect of inclination angle on performance of the sensor. Findings - The theoretical result shows that the highest sensitivity can be achieved by using a probe inclined with angle 20° which is almost 13 times higher than that of 0° inclination. In the experiment, three different liquids: isopropyl alcohol, water and methanol are used to investigate the sensor response. Both theoretical and experimental results show that the peak power and the location of the displacement curve changes with refractive index. The sensitivities are obtained at 0.11/mm and 0.04/mm for the sensors with 10° and 0° inclination angles, respectively. Originality/value - In this paper, a simple LRIS is proposed using a bundle fiber as a probe at various inclination angles.